Efektivitas Modul Pembelajaran Berbasis Islami Materi Hak dan Kewajiban terhadap Hasil Belajar Siswa Kelas IV SDS Muhammadiyah 32 Medan - Akhirunnisa Hasibuan; Melyani Sari Sitepu (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
The teaching and learning process will take place effectively and efficiently if the learning process is carried out in the presence of good learning resources, one of which is the Islamic-based rights and obligations learning module. Based on observations made, learning outcomes and student activities have not been effective. The lack of use of learning devices is one of the reasons. Based modules are devices used to make students understand and know more based on the Koran and hahdits. The purpose of this study is to determine the effectiveness of the Islamic-based rights and obligations module in class V SDS Muhammadiyah 32 Medan. This study used an experimental method using one class as a sample. Collecting data in this study by observation and tests. The resulting data were analyzed using the t-test formula. The results of the t-test analysis using a significant level of 5% indicate that the sig (2-tailed) module of Islamic-based rights and obligations learning on student learning outcomes and activities is 0.000 <0.05 so it can be concluded that the use of Islamic-based rights and obligations modules is effectively used in the learning process.